Annexin A3 as a Prognostic Biomarker for Breast Cancer: A Retrospective Study. (13th April 2017) - Zhou, Tao; Li, Yong; Yang, Li; Tang, Tiantian; Zhang, Lina; Shi, Jiajie
Abstract : To validate the correlation between ANXA3 expression and prognosis in breast cancer, a retrospective study encompassing 309 breast cancer patients was performed. The expression of ANXA3 was determined by the immunohistochemical examination of tissue sections by the Max Vision™ method. The ANXA3 levels in the patient samples were validated for the prognosis based on age, menopause status, tumor size, tumor node, metastasis stage, the number of lymphatic metastases, oncology grade, and molecular subtyping. An elevated expression of ANXA3 was detected in breast cancer samples, compared to adjacent tissue samples, and significant correlation depending on the number of lymphatic metastases (P = 0.001 ) and histological grade (P = 0.004 ) was observed. The number of lymphatic metastases and ANXA3 expression were identified as independent risk factors affecting the disease-free survival and overall survival. Significantly (P < 0.002 ) higher level of ANXA3 was detected in triple-negative breast cancer compared to other subtypes. There was no significant (P > 0.05 ) change in the expression of ANXA3 with respect to age, menopausal status, tumor size, and clinical stage. The findings implicate the expression of ANXA3 with the natural progression of breast cancer and associate it with increased lymphatic metastasis. The study validates the use of ANXA3 as a potential prognosis biomarker for breast cancer.